THE FINANCING OF HEALTH CARE IN UKRAINE - Savchuk , L.M. (The actual problems of regional economy development, 2016)
In the article the peculiarities of financing healthcare in Ukraine. Analyzed various sources of funding for the sector. Health expenditure per capita of the population in Ukraine and around the world have been investigated. On the basis of the analysis found that the size of budget financing are inefficient and do not meet the resource needs of the industry. Clarified the problems of resource provision of health care and the shortcomings of public Finance mechanisms. Asked to review the existing allocation mechanism of the industry and the rapid transition to a model of budgetary-insurance medicine. JEL: H 51